Effects of Production and Operating Costs on Net Profit on Manufacturing Companies Registered in JII - Arbarija Hafiz Lubis; Sugianto, Sugianto; Kusmilawaty, Kusmilawaty (Dinasti Publisher, 2024)
This research aims to determine the influence of production costs and operational costs on net profit in manufacturing companies listed on the Jakarta Islamix Index (JII) for the 2018-2022 period by classifying sharia stock index companies that operate in the consumption sector. Quantitative research methods are descriptive and verification approaches that describe a variable based on quantitative data analysis with statistical procedures to test a research data hypothesis. The data analysis technique used is panel data regression analysis. Hypothesis tests used include the T test, F test, and coefficient of determination. And data processing is assisted with the E Views for Windows Version 12.00 device. The samples studied were 7 manufacturing companies at JII in the last 5 years (2018-2022). The research results are based on an analysis of manufacturing companies listed on the Jakarta Islamic Index (JII) in 2018 - 2022. Production costs (X1) partially have no significant negative effect on Net Profit (Y) and operational costs (X2) partially have a significant positive effect on Net Profit (Y). Production costs (X1) and operational costs (X2) simultaneously do not have a significant effect on Net Profit (Y).